Rise of the Global South and Its Impact on South-South Cooperation - Singh Puri, Hardeep (2012)
Over the past two decades, a fundamental transformation has taken place in the global economy caused by the impressive economic growth of developing countries like China, India, Brazil, and South Africa. The economic center of gravity is inexorably moving toward the developing South. The remarkable upsurge in cooperation between developing countries, characterized as South-South cooperation, must be understood as part of this larger story.